Microarray Strategies for Exploring Bacterial Surface Glycans and Their Interactions With Glycan-Binding Proteins - Campanero-Rhodes, María Asunción (2021)
Spanish Ministry of Economy and Competitiveness (Grant BFU2015-70052-R). Spanish Ministry of Science, Innovation, and Universities, the Spanish State Research Agency, the European Regional Development Fund (RTI2018-099985-B-I00, MCIU/AEI/FEDER, UE), the CIBER of Respiratory Diseases (CIBERES), an initiative from the Spanish Institute of Health Carlos III (ISCIII). PTDC/BIA-MIB/31730/2017. IF/00023/2012. Applied Molecular Biosciences Unit (UCIBIO) (Financed by FCT-MCTES, UID/Multi/04378/2013/2019).